PENGEMBANGAN MODUL DIGITAL ELEKTRONIKA DASAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN TEKNOLOGI DASAR OTOMOTIF DI SMK MUHAMMADIYAH 3 YOGYAKARTA - Robertus Armando Godat; setuju (JURNAL VOKASI DEWANTARA (JVD), 2024)
This study aims to determine the feasibility of a good and quality basic electronic digital module. This research is development research. The research model has 4 stages in the research, namely define, design, develop and desseminate. Educational materials (learning modules) for Basic Automotive Technology subjects were validated by 2 material experts and 2 media experts, then tested on 42 students of class X majoring in Light Vehicle Engineering at Vocational High School (SMK) Muhammadiyah 3 Yogyakarta. Collecting data using a 4-preference Likert scale questionnaire/questionnaire. The results of the module expert assessment are 3.09 from the optimal score of 4 so that they are listed in the "decent" category, the average total score from the results of the media expert assessment is 3.33 from the optimal score of 4 so that it is listed in the "decent" category, the average the average total score from the results of the field test is 3.14 from the optimal score of 4 so that it is listed in the "good" type, so that the average totality of the results of the assessment by module experts, media experts, and field tests gets an average score of 3.19 from a maximum score of 4 so that it is listed in the "decent/good" category.